Model RelasiSosial Ekonomi Jagal, Sawi dan Peternak dalam Perdagangan Daging Sapi di Kabupaten Sumbawa, Nusa Tenggara Barat - Soekardono Soekardono; Muhammad Yasin; Anwar Fachry; Muhammad Prasetyo Nugroho; Hermansyah Hermansyah (Faculty of Animal Husbandry, University of Mataram, 2016)
This study aimed to analyze a model of economic social relationships between slaughter, sawi (women mealtraders in a traditional market) and cattle farmers in Sumbawa, West Nusa Tenggara. Another objective was toassessthe causative factors for changing of economic social relationship between of these actors in beeftrading. Data were analyzed using descriptive approaches. The results of the study show that economic-socialrelationships between slaughter, sawiand cattle farmers tended to weaken in the last five years. Loosening ofsocial relations was caused by similarity and familial patterns that had been neglected. These actors were moreprofit-oriented than maintaining of social relationships. The other causative factors were due to the pressure ofoutside competitors with the increasing number and a lot of financial capability. The competitors ofSumbawa’s slaughter were not only the local actors but also slaughter and cattle traders from Lombok whosehad made cattle purchase increased to remote areas in Sumbawa.